Inhibition of Propionibacterium acnes by refined bamboo vinegar and preparation of the slow-release system with bamboo charcoal as the carrier - Ziyi Li; Yanan Wang; Sheng Zhang (Journal of Dermatologic Science and Cosmetic Technology)
Background: Acne vulgaris is one of the most common skin diseases that can significantly impact a considerable proportion of individuals over their lifetime. Objective: This study focuses on the exploration of the application potential of bamboo vinegar in cosmetics. Materials and Methods: The stock solution of bamboo vinegar is subjected to reduced-pressure distillation at different temperatures to obtain refined bamboo vinegar. Then, inhibition of Propionibacterium acnes (P. acnes) by refined bamboo vinegar is observed. Moreover, the refined bamboo vinegar is adsorbed and released with activated bamboo charcoal as the carrier. In all, this study aims to probe into the mechanism of the controlled-release system of bamboo vinegar. Results: The results shows that the harmful substances (tar) in bamboo vinegar distilled at 70 ℃ decreased by 94.44%, which is a more notable decrease compared with that in the stock solution. The total organic acid content in bamboo vinegar after reduced-pressure distillation is 11.840%, reaching the national standard for refined bamboo vinegar (GB/T 31734–2015).Additionally, the minimum inhibitory concentration of refined bamboo vinegar against P. acnes using the punch method is 7.90 mg/mL. This indicates that refined bamboo vinegar has the potential as a prospective raw material for formulations in anti-acne cosmetic products. Furthermore, the release rate of bamboo charcoal/bamboo vinegar in water for 15 min reaches 70.57%, which then slows down to a plateau. The slow-release behavior is agreed with the Ritger-Peppas model and is beneficial to relieve the irritation of bamboo vinegar to the skin and lengthen its bacteriostatic duration. Conclusion: The foregoing conclusions can serve as the theoretical foundation for the application of bamboo vinegar in anti-acne cosmetics.